The Extent Of The Applicability And Compulsion Of International Humanitarian Law In The Cyberwarfare - صفطلي مايا; الدقاق نجاح (Latakia University Journal - Economic and Legal Sciences Series, 2022)
After the four Geneva Conventions for the Protection of Victims of Armed Conflicts of 1949 and the Additional Protocols attached thereto of 1977 laid the foundations of the rules of contemporary international humanitarian law, and its provisions are no longer subject to controversy, whether in terms of the provisions of those rules or in terms of their binding for the parties to both international and non-international armed conflict; The controversy arises again and from time to time whenever a new type of confrontation arises between the parties to the conflict, whether in its form or its tools, in order to find out whether this new confrontation that has developed is a type of armed conflict and whether the provisions of international humanitarian law apply to it accordingly as well. Cyber-attacks constitute one of the subjects of this controversy in international jurisprudence and jurisdiction today, as we can attribute it to one reason, which is the absence of international legal rules regulating its provisions. So that one group says that Cyber-attacks are not subject to the provisions of the rules of international humanitarian law, and another group says that they occur, and this is what prompted the research into those problems that hinder the application of the provisions of international humanitarian law in the absence of texts regulating its provisions to know the consequences and to avoid the negative ones and prevent their occurrence.